The clinical and cost-effectiveness of stratified care for patients with sciatica: the SCOPiC randomised controlled trial protocol (ISRCTN75449581) - Nadine E. Foster; Kika Konstantinou; Martyn Lewis; Reuben Ogollah; Kate M. Dunn; Danielle van der Windt; Ruth Beardmore; Majid Artus; Bernadette Bartlam; Jonathan C. Hill; Sue Jowett; Jesse Kigozi; et al. (BMC Musculoskeletal Disorders, 2017)
Abstract Background Sciatica has a substantial impact on patients, and is associated with high healthcare and societal costs. Although there is variation in the clinical management of sciatica, the current model of care usually involves an initial period of ‘wait and see’ for most patients, with simple measures of advice and analgesia, followed by conservative and/or more invasive interventions if symptoms fail to resolve. A model of care is needed that does not over-treat those with a good prognosis yet identifies patients who do need more intensive treatment to help with symptoms, and return to everyday function including work. The aim of the SCOPiC trial (SCiatica Outcomes in Primary Care) is to establish whether stratified care based on subgrouping using a combination of prognostic and clinical information, with matched care pathways, is more effective than non-stratified care, for improving time to symptom resolution in patients consulting with sciatica in primary care. We will also assess the impact of stratified care on service delivery and evaluate its cost-effectiveness compared to non-stratified care. Methods/Design Multicentre, pragmatic, parallel arm randomised trial, with internal pilot, cost-effectiveness analysis and embedded qualitative study. We will recruit 470 adult patients with sciatica from general practices in England and Wales, over 24 months. Patients will be randomised to stratified care or non-stratified care, and treated in physiotherapy and spinal specialist services, in participating NHS services. The primary outcome is time to first resolution of sciatica symptoms, measured on a 6-point ordered categorical scale, collected using text messaging. Secondary outcomes include physical function, pain intensity, quality of life, work loss, healthcare use and satisfaction with treatment, and will be collected using postal questionnaires at 4 and 12-month follow-up. Semi-structured qualitative interviews with a subsample of participants and clinicians will explore the acceptability of stratified care. Discussion This paper presents the details of the rationale, design and processes of the SCOPiC trial. Results from this trial will contribute to the evidence base for management of patients with sciatica consulting in primary care. Trial registration ISRCTN75449581 , date: 20.11.2014.